Konstruksi Puasa Waqi'ah - Muhammad Anwar Idris (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
Fasting is divided into at least two groups, namely required fasting and non-required fasting. The only fast that is required in Islam is fasting during Ramadan. In addition to fasting on Mondays and Thursdays, there is one type of fasting done at Pondok Pesantren an- Nur 1, Bululawang, Malang, East Java, which is interesting. Motivation, method of implementation, history, transmission- transformation of Waqi'ah fasting are special and far different from other non-required fasts. The interview, observation, documentation, and utilization of the living hadith approach used in this study, is able to uncover the fact that this fast is a